1989
DOI: 10.1002/eji.1830190721
|View full text |Cite
|
Sign up to set email alerts
|

Biased immunoglobulin variable region gene expression by Ly‐1 B cells due to clonal selection

Abstract: Most, if not all, autoantibodies specific for bromelain-treated mouse erythrocytes recognize the common membrane phospholipid, phosphatidyl choline (PtC). Anti-PtC antibodies are produced by 5%-15% of CD5+ Ly-1 B cells of normal unimmunized mice, but not by detectable numbers of conventional CD5- B cells. At 1 week of age PtC-specific B cells are undetectable but then increase dramatically over the next 3 to 4 weeks to reach adult numbers. We report here that PtC-specific Ly-1 B cells in B10.H-2aH-4bp/Wts mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
103
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 53 publications
7
103
0
Order By: Relevance
“…However, when we analyzed rearrangements of the much smaller V H 12 family, we obtained a striking result. As noted above, the predominant V H 12-containing H chain, found paired with a V 4 ϩ L chain in the peritoneal anti-PC B-1 cell subset, consists of a V H 12-D H -J H 1 rearrangement containing a 10-aa CDR3 (42). In three independent experiments, we found that rAnV ϩ immature B cell populations consistently contain a dominant V H 12 to DJ H 1 rearrangement that comigrates with the product from the V H 12 transgene and with the corresponding positively selected V H 12 H chains in control nonTg PerC, day 6 spleen, and adult spleen (Fig.…”
Section: Recombinant Anv Marks Selected Pro-b and Immature B Cellsmentioning
confidence: 73%
See 2 more Smart Citations
“…However, when we analyzed rearrangements of the much smaller V H 12 family, we obtained a striking result. As noted above, the predominant V H 12-containing H chain, found paired with a V 4 ϩ L chain in the peritoneal anti-PC B-1 cell subset, consists of a V H 12-D H -J H 1 rearrangement containing a 10-aa CDR3 (42). In three independent experiments, we found that rAnV ϩ immature B cell populations consistently contain a dominant V H 12 to DJ H 1 rearrangement that comigrates with the product from the V H 12 transgene and with the corresponding positively selected V H 12 H chains in control nonTg PerC, day 6 spleen, and adult spleen (Fig.…”
Section: Recombinant Anv Marks Selected Pro-b and Immature B Cellsmentioning
confidence: 73%
“…They are driven to expand from birth, and eventually account for 2-10% of the peritoneal B-1 repertoire in normal adults. IgM specific for PC is encoded predominantly by either of two combinations of V H and V L : V H 11 and V 9 (41) or V H 12 and V 4 (42). In the case of V H 12 ϩ PC-reactive B-1 cells, the V H 12 H chain is further characterized by a complementarity-determining region 3 (CDR3) that is invariably 10 aa in length (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these cells were found within the CD5 ϩ population in the adult. Previously, in adult mice, B cells with canonical receptors containing particular V H -D-J H /V -J junctions were reported in association with the B1 phenotype (22,45,46). In addition, selection of certain V H -J -bearing clones into the mature long-lived B cell pool (46), and BCR-directed selection of V H 81x-V 1C and V H S107-V 24 clones into the splenic marginal zone were recently reported (47).…”
Section: Discussionmentioning
confidence: 97%
“…In these studies, B-1 cell development appeared to correlate with Ag receptor specificity. Recognition of self Ag, either endogenously or transgenically expressed, was shown to be necessary for the generation and expansion of the B-1 cell population (18,21,23). The pleural and peripheral compartments of these mice become replete with cells bearing the B-1 phenotype.…”
mentioning
confidence: 99%